Recent Advances in Operator Theory and Applications
DOI: 10.1007/978-3-7643-8893-5_3
|View full text |Cite
|
Sign up to set email alerts
|

Some Problems Concerning the Test Functions in the Szegö and Avram-Parter Theorems

Abstract: The Szegö and Avram-Parter theorems give the limit of the arithmetic mean of the values of certain test functions at the eigenvalues and singular values of Toeplitz matrices as the matrix dimension increases to infinity. This paper is concerned with some questions that arise when the test functions do not satisfy the known growth restrictions at infinity or when the test function has a logarithmic singularity within the range of the symbol. Several open problems are listed and accompanied by a few new results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Note that Golinskii and Ibragimov [3] proved that the so-called strong Szegő limit theorem for positive generating functions is indeed true whenever it makes sense (see also the books [2] and [6]). In [1] we showed that the answer to our question is negative: ST and APT are proper subsets of C + (R) and C + [0, ∞), respectively.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…Note that Golinskii and Ibragimov [3] proved that the so-called strong Szegő limit theorem for positive generating functions is indeed true whenever it makes sense (see also the books [2] and [6]). In [1] we showed that the answer to our question is negative: ST and APT are proper subsets of C + (R) and C + [0, ∞), respectively.…”
mentioning
confidence: 93%
“…The counterexample in [1] is highly oscillating and leaves us with the question whether ST and APT contain at least all monotonous functions. Our first main result tells us that, surprisingly, this is not the case: The proof of this theorem is rather sophisticated.…”
mentioning
confidence: 98%
See 1 more Smart Citation